KOMUNIKASI LINTAS BUDAYA DAN FAKTA ETNIS CINA DI INDONESIA SEBAGAI BUKTI KOMUNIKASI LINTAS BUDAYA - Riefky Krisnayana (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2016)
Communication Cross-culture is the process by which diverted the idea or the idea of a culture of the culture of the other and vice versa, and it can be between two cultures associated or more, in order to influence each other, whether it's for the good of a culture or to destroy a culture, or it could be an initial step of the process of acculturation (the merger of two cultures or that generate new culture).